DOP88 Effect of risankizumab on patient-reported outcomes in patients with Crohn's Disease who had an inadequate response or intolerance to conventional and/or biologic treatments: Results from phase 3 MOTIVATE and ADVANCE trials. (27th May 2021) - Peyrin-Biroulet, L; Louis, E; Ghosh, S; Lee, S D; Griffith, J; Wallace, K; Berg, S; Loftus, E V
Abstract: Background: Risankizumab (RZB), an IL-23 inhibitor, is being investigated for Crohn's disease (CD). MOTIVATE (NCT03105128) and ADVANCE (NCT03104413) were two double-blind, randomised, placebo (PBO)-controlled phase 3 trials evaluating the efficacy and safety of RZB as induction therapy for CD after inadequate response or intolerance to biologic treatment, or conventional or biologic treatment. We investigated the effect of RZB on patient-reported outcomes (PROs) in these two trials. Methods: Patients with moderately to severely active CD (CD activity index of 220–450, Simple Endoscopic Score for CD excluding the narrowing component ≥ 6 or ≥ 4 for isolated ileal disease, and average daily stool frequency ≥ 4 and/or average daily abdominal pain score ≥ 2) were randomised 1:1:1 (MOTIVATE; N=569) or 2:2:1 (ADVANCE; N=850) to intravenous RZB 600 mg, RZB 1200 mg or PBO at Weeks 0, 4 and 8. PROs assessed were Inflammatory Bowel Disease Questionnaire (IBDQ), Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F), and 36-Item Short Form Health Survey (SF 36). Least-squares mean change from baseline to Week 4 and 12 were assessed for each PRO. Additionally, the proportion of patients achieving IBDQ remission (IBDQ total score ≥ 170 points) was evaluated. Comparisons between RZB dosage groups and PBO were based on Cochran-Mantel-Haenszel or chi-square/Fisher's exact tests; missing data were reported using non-responder imputation. Results: In the MOTIVATE (100% biologic inadequate responder [bio-IR]) and ADVANCE (57% bio-IR) trials, significant ( P <0.05) improvements in nearly all PROs evaluated were seen as early as Week 4 (Figures 1–4). At Week 12, significant improvements in all PROs were reported for both doses of RZB compared with PBO in both trials, except for the SF-36 Mental Component Summary score (RZB 1200 mg in MOTIVATE), which improved, but not significantly. In MOTIVATE, at Week 4 and 12, IBDQ remission was achieved by significantly ( P <0.05) more patients taking RZB (600 mg, 25.1%/38.3%; RZB 1200 mg, 31.9%/44.6%) than PBO (15.5%/26.8%). Results were similar in ADVANCE: RZB 600 mg 30.9%/44.5%, RZB 1200 mg 33.7%/51.5%, and PBO 18.4%/29.8% at weeks 4 and 12, respectively ( P <0.001 for both RZB groups compared to PBO). Conclusion: Patients with active CD and an inadequate response to conventional or biologic treatment who received RZB (600 mg or 1200 mg) induction therapy reported significant improvements in disease-specific (IBDQ) and general health-related PROs (FACIT and SF-36) compared with PBO, with improvements seen as early as Week 4. Funding statement: Study was funded by AbbVie. Acknowledgement: Medical writing support was provided by Joann Hettasch of Fishawack Facilitate Ltd, and was funded by AbbVie.